Respuestas

2014-03-03T21:18:05+01:00
  3x -1   = 2x + 5 
          3(6)-1  = 2(6) + 5    <Se sustituyó el x por el 6> 
          18 - 1  = 12 + 5       <Se resuelve en ambos lados> 
                17 = 17 

 3x + 1    = 2x + 3 
          3(3) + 1 = 2(3) + 3 
          9 + 1     = 6 + 3 
                  10 = 9 

 3x + 9 = 2x - 3 
           3x + 9 = 2x + -3 
          3x - 2x = -9 + -3             <Al sumar queda la x sola por lo 
                                            tanto x = -12 
                  x = -12 

Espero ayudaarte besos..
2014-03-03T21:20:25+01:00
 3x -1   = 2x + 5 
          3(6)-1  = 2(6) + 5    <Se sustituyó el x por el 6> 
          18 - 1  = 12 + 5       <Se resuelve en ambos lados> 
                17 = 17 

 3x + 1    = 2x + 3 
          3(3) + 1 = 2(3) + 3 
          9 + 1     = 6 + 3 
                  10 = 9 




 3x + 9 = 2x - 3 
           3x + 9 = 2x + -3 
          3x - 2x = -9 + -3             <Al sumar queda la x sola por lo 
                                            tanto x = -12 
                   x = -12 



 2x + 5   = 1 
               2x  = 1 + - 5 
                2x -4 
              2       2
                  x = -2